PENGARUH FAKTOR-FAKTOR FUNDAMENTAL TERHADAP RETURN SAHAM PADA INDUSTRI OTOMOTIF DAN KOMPONENNYA DI BURSA EFEK INDONESIA PERIODE 2011-2016 - Andrea Alvionata Heryanda; Fajri Andrianto (Politeknik Negeri Lhokseumawe, 2020)
The title of this research is “The effect Fundamental Factors to Stock Return of Automotive and allied Industry in Indonesia Stock Exchange period 2011-2016 ”. The aims of this research are to know are fundamental facktors have influence which is sigificant in simultan and partial to stock return, and to know which of the variable dominant have an effect which is significant to common price of Automotive and allied Industries in Indonesia Stock Exchange period 2011-2016. In this Research there are 12 firms. This researches used secondary data collected by using library research method, and for analysis test the researches used Panel data method. Analysisi tools used are a “f” test, “t” test, and coeffisient of determination. Based on “t” test the research know that in partial only Return On Asset have influence which is sigificant to stock return. Based on coefficient of determination know that amount of current ratio, debt to equtity ratio, total asset turn over, return on asset dan price earning ratio have not influence which is significant in simultant to stock return. We know that for return on asset most influences on Stock return. Keyword : Current Ratio, Debt to Equity Ratio, Total Asset Turn Over, Return On Asset, Price, Earning Ratio and Stock Return